Imagining Marshall McLuhan as a digital reader: an experiment in applied Joyce. Issue 9 (2nd September 2021) - Galey, Alan
ABSTRACT: Was Marshall McLuhan's greatest work not his published writing but his reading? This article examines McLuhan's annotation practices in his copies of James Joyce's Ulysses and A Portrait of the Artist as a Young Man, and asks what kinds of evidence a prolific annotator like McLuhan might have left if he had done his reading digitally. The first half profiles McLuhan's annotation practices, illustrated by examples from books from McLuhan's personal library. The second half describes an informal experiment, in which the author tests McLuhan's annotation techniques against the capabilities of digital book platforms and formats, specifically PDF (using the Apple Preview app) and EPUB (using the Apple Books app). Overall, the article works through two questions that are relevant to book history, marginalia studies, and digital archiving. How will we understand the evidence left behind by readers when that evidence is in born-digital forms, as archived digital files? And what can we learn about digital reading and annotation from someone like McLuhan, who did those things exceptionally well in another medium? The conclusion reflects on prospects for the study of born-digital marginalia, and on the role of encyclopedism in understanding both McLuhan's and Joyce's media theory.